1991
DOI: 10.1021/jm00107a046
|View full text |Cite
|
Sign up to set email alerts
|

1H-Imidazo[4,5-c]quinolin-4-amines: novel non-xanthine adenosine antagonists

Abstract: On the basis of a model we recently developed for the antagonist binding site of the adenosine A1 receptor (J. Med. Chem. 1990, 33, 1708-1713), it was predicted that 1H-imidazo[4,5-c]quinolin-4-amines would be antagonists of the A1 receptor. Furthermore, it was expected that certain hydrophobic substitutions at the 2- and 4-positions would enhance affinity. Here, we report on the synthesis and the adenosine A1 and A2 receptor affinity of substituted 1H-imidazo[4,5-c]quinolin-4-amines. Some of these compounds h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
77
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 8 publications
3
77
0
Order By: Relevance
“…The imidazoquinoline analogs were tested in competitive binding assays at human A 3 receptors, and K i values ranging from 120 nM to 101 M were observed; as for many allosteric modulators of GPCRs, an orthosteric competitive effect was also present. One of the compounds, DU124482, was suggested to be a selective A 1 receptor antagonist (van Galen et al, 1991); the present study further confirmed this selectivity by virtue of weak affinity at A 3 receptors.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The imidazoquinoline analogs were tested in competitive binding assays at human A 3 receptors, and K i values ranging from 120 nM to 101 M were observed; as for many allosteric modulators of GPCRs, an orthosteric competitive effect was also present. One of the compounds, DU124482, was suggested to be a selective A 1 receptor antagonist (van Galen et al, 1991); the present study further confirmed this selectivity by virtue of weak affinity at A 3 receptors.…”
Section: Discussionsupporting
confidence: 76%
“…These imidazoquinoline derivatives were first reported as antagonists of A 1 and A 2A receptors (van Galen et al, 1991). The imidazoquinoline analogs were tested in competitive binding assays at human A 3 receptors, and K i values ranging from 120 nM to 101 M were observed; as for many allosteric modulators of GPCRs, an orthosteric competitive effect was also present.…”
Section: Discussionmentioning
confidence: 99%
“…van Galen et al (1991) originally introduced the imidazoquinolinamines as A 1 receptor antagonists. In addition to orthosteric binding competitive with the native ligand adenosine, the compound DU124183 was an allosteric enhancer of radioligand binding at the A 3 adenosine receptor.…”
Section: Nomenclature and Classification Of Adenosine Receptorsmentioning
confidence: 99%
“…High-yielding arylations are possible not only with aryl bromides but also with aryl iodides (Table 2, entries 17 and 18) and even with aryl chlorides (entries [13][14][15][16]. With aryl iodides, Ag 2 CO 3 must be employed as an additive.…”
Section: Entry 3)mentioning
confidence: 99%
“…[14] A second direct arylation can add a second aromatic group as in the formation of 9. Alternatively, the N-oxide may be converted to chloropyrazine 10 by reaction with POCl 3 [15] and subsequently used in a wide range of palladium catalyzedcross coupling reactions. To illustrate this possibility, a Buchwald-Hartwig amination was performed, giving 11 in 70 % yield.…”
Section: Entry 3)mentioning
confidence: 99%